Speech Configuration and its Aesthetic Aspects (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article is devoted to the study of the aesthetic aspects of speech configuration. Speech can be considered not only as a means of transmitting information, but also as a work of art. The article analyzes the aesthetic effects created by the structural elements of speech, namely rhythm, intonation, lexical and syntactic choices. The aesthetic aspects of speech configuration are discussed, how it affects the listener, how it expresses emotions and what role it plays in the communication process. The article also examines the perception of speech as a work of art, its aesthetic value and place in the cultural context.